IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PEMILIHAN SMARTPHONE TERBAIK DENGAN WEIGHT PRODUCT (WP) (STUDI KASUS PADA MAHASISWA STMIK GICI) - Habibie, Dedi Rahman (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2018)
AbstractWeighted Product (WP) Weigthted Product is a method of completion by using multiplication to attribute attribute rating, where the rating must be raised first with the attribute weights in question. This process is equal to. Weighted Product (WP) is used to help make the best mobile phone determination then the brand of mobile phone purchased (Iphone, Samsung, Oppo. and Lenovo), need some criteria. Criteria are price, technology and design price of product, spare parts, and reselling. Technology goes down to camera, features, and battery. The design is lowered to qwerty, touchscreen and common touch.Keywords : Weighted Product (WP), SmartPhone, Alternative, Criteria